2017
DOI: 10.1152/japplphysiol.00935.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness modulates the acute flow-mediated dilation response following high-intensity but not moderate-intensity exercise in elderly men

Abstract: 39Impaired endothelial function is observed with ageing and with low cardiorespiratory fitness 40 (VO 2peak ) whilst improvements in both are suggested to be reliant on higher-intensity exercise in 41 the elderly. This may be due to the flow-mediated dilation (FMD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 77 publications
1
35
1
Order By: Relevance
“…Furthermore, while it may appear that scaled FMD increased by 0.9% from baseline to 24 h post‐exercise in men, examining the individual participant responses revealed that only two men were driving this change. Our findings are in contrast to previous reports that endothelial function increases between 1 and 24 h post‐exercise before returning to baseline levels by 24–48 h (Dawson et al., ) and to previously observed increases of 1–8% in endothelial function after higher‐volume interval protocols (Bailey et al., ; Bond et al., ; Chuensiri et al., ; Francois et al., ). Increases in brachial artery FMD of 1–1.5% have been deemed clinically and physiologically relevant (Inaba et al., ; Tinken et al., ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Furthermore, while it may appear that scaled FMD increased by 0.9% from baseline to 24 h post‐exercise in men, examining the individual participant responses revealed that only two men were driving this change. Our findings are in contrast to previous reports that endothelial function increases between 1 and 24 h post‐exercise before returning to baseline levels by 24–48 h (Dawson et al., ) and to previously observed increases of 1–8% in endothelial function after higher‐volume interval protocols (Bailey et al., ; Bond et al., ; Chuensiri et al., ; Francois et al., ). Increases in brachial artery FMD of 1–1.5% have been deemed clinically and physiologically relevant (Inaba et al., ; Tinken et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…Although acute increases in brachial FMD have been previously observed with interval exercise (Bailey et al, 2017;Bond et al, 2015;Chuensiri et al, 2015;Currie et al, 2012;Francois et al, 2016), these exercise paradigms involved longer intervals at submaximal intensities An unanticipated finding in this study was the observation of a slight attenuation in some resting and RH haemodynamic parameters at 1 h post-exercise. While SR AUC remained unchanged and time to peak dilatation tended to be longer at 1 h post-exercise, the attenuations in BF (resting BF, peak RH BF, and postdeflation BF averaged to the peak RH diameter) and MBV all seem to suggest that we may have captured the tail end of haemodynamic recovery.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations